Peningkatan Edukasi Kesehatan Santri Tahfidzil Qur’an Desa Podorejo Tulungagung Dalam Rangka Pencegahan Covid-19 dengan Mengkonsumsi Sayur, Buah dan Bahan Rempah-Rempah Untuk Meningkatkan Imunitas Tubuh - Rohmatul Hidayah; Mega Dwi Susanti (LP3M IAIFA Kediri, 2021)
During a pandemic like this, many people consume too many chemical drugs which will have an impact on health which will gradually have a bad impact, such as the kidneys, heart, will not function if they continue to be attacked by chemical drugs. During this COVID-19 pandemic, people need good medicine for their health now and in the future, such as consuming spices that can be processed into traditional drinks of old. Many spices are good for consumption during a pandemic like this, such as ginger, kencur, turmeric, temulawak, lempuyang, etc. In consuming spices, it can be used as instant powder ready for brewing which can last a long time if consumed every day. Many Tahfidzil Qur'an students consume traditional herbal medicine or consume spices that have been cooked into an instant powder that is ready to brew with a manufacturing process that takes approximately 1 hour.